Bioethical Issues in Human Modification for Protection against the Effects of Space Radiation. (November 2022) - Szocik, Konrad; Braddock, Martin
Abstract: Protection against the effects of space radiation poses great technical and medical challenges for future human missions and is of interparliamentary concern requiring alignment of multiple scientific, clinical, and ethical parameters. In our article, we highlight the inadequacy of current countermeasures, which may justify the use of human enhancement (HE), or biomedical technologies to increase astronaut protection from the harmful space environment, protect lifespan longevity and increase the chance of survival during spaceflight or as colonists on other worlds. The deleterious effects of space radiation on the human body may justify even the most radical forms of HE, which may incorporate gene editing. As a thought experiment, we propose that an ethical assessment should depend on the anchor and purpose of the mission and we discuss differences and similarities between the bioethics of space missions and military ethics on Earth.